The Effect of Perception Exercise of Tactual Sally Mangold toward Early Reading Capability for Students with Hearing Impairment - Putri Nur Hakiki; Endro Wahyuno (Department of Special Education, 2017)
Visual Impairment is obstacle in vision function that requires a different way of learning with other normal person. Visual impairment have the tools to learn how to read and writing like braille. Reading is activity that is needed to get the information. The objective of this study is to describe the effect of sally mangold tactual perception exercise toward subject’s early reading ability that viewed from before and after intervention. The method was experiment of single subject reasecrh design with A-B-A model. The conclusion of this study was found a positive effect of Sally Mangold tactual perception exercise toward subject’s early reading ability. The positive effect was seen from the increase score subject’s early reading ability from 50% to 98%.Tunanetra merupakan hambatan fungsi pengelihatan yang membutuhkan cara belajar yang berbeda dengan orang normal lainnya. tunanetra memiliki alat untuk belajar membaca dan menulis disebut braille. Membaca adalah kegiatan yang diperlukann untuk mendapatkan informasi. Tujuan dari penelitian ini adalah mendeskripsikan pengaruh latihan persepsi taktual Sally Mangold terhadap kemampuan membaca permulaan subyek dilihat dari sebelum dan sesudah intervensi. Metode yang digunakan adalah eksperimen dengan desain Single Subyek Resecrh dan model A-B-A. Kesimpulan dari penelitian ini ditemukan pengaruh positif latihan persepsi taktual Sally Mangold terhadap kemampuan membaca permulaan subyek. Pengaruh tersebut dilihat dari skor kemampuan membaca permulaan subyek dari 50% menjadi 98%.DOI: http://dx.doi.org/10.17977/um029v4i12017p069